2021
DOI: 10.1111/dth.14855
|View full text |Cite
|
Sign up to set email alerts
|

Prurigo nodularis comparative treatment outcome in patients attending a tertiary hospital in northern Tanzania

Abstract: Prurigo nodularis (PN) is a chronic, benign neurodermatitis of unclear etiology characterized by excoriated, intensely pruritic nodules secondary to an intense itch-scratch cycle. PN treatment is still a challenge, and it is frustrating for both dermatologists and patients. The evidence for the effectiveness of a readily available treatment like cryotherapy is limited. To compare the efficacy of cryotherapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…8 In a prospective study on cryotherapy, all 11 patients enrolled reported 75% to 100% clearance of pruritic nodules after treatment. 9 A prospective study on vitamin D analogue tacalcitol showed improvement of symptoms in 3 out of 4 patients. 10 Another prospective study on vitamin D analogue calcipotriol showed a significant reduction in the number and size of lesions in 10 patients after 8 weeks as compared to betamethasone ointment.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…8 In a prospective study on cryotherapy, all 11 patients enrolled reported 75% to 100% clearance of pruritic nodules after treatment. 9 A prospective study on vitamin D analogue tacalcitol showed improvement of symptoms in 3 out of 4 patients. 10 Another prospective study on vitamin D analogue calcipotriol showed a significant reduction in the number and size of lesions in 10 patients after 8 weeks as compared to betamethasone ointment.…”
Section: Resultsmentioning
confidence: 97%
“…10,11 Studies on cryotherapy supported its use as PN treatment with results showing resolution of symptoms in all patients enrolled. 9,26,27…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In Tanzania, however, prurigo nodularis is reported to be treated by conventional means. 3 Their study presented work done in their center using conventional medicine and did not examine what, if any therapies are used by those that may have no access to such therapies. As a result, no information on traditional therapies for this disorder was reported.…”
mentioning
confidence: 99%